Water Security in Rural India: Examining Water Security in Major States of India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
‘This paper is an attempt to describe the different levels of water security in major states of India. The study includes India as a whole and major states such as Haryana, Rajasthan, Utter Pradesh, West Bengal, Jharkhand Odisha, Madhya Pradesh, Gujrat, Maharashtra, Andhra Pradesh, Karnataka, Tamil Nadu, Kerala, Bihar and Punjab.’